Assistance to families of children with Autism Spectrum Disorders: Perceptions of the multiprofessional team - Tassia de Arruda Bonfim; Bianca Cristina Ciccone Giacon-Arruda; Sueli Aparecida Frari Galera; Elen Ferrraz Teston; Francisneide Gomes Pego Do Nascimento; Maria Angélica Marcheti (Universidade de São Paulo, 2023)
Abstract Objective: to synthesize the care provided by health professionals, at different care levels, to the families of children with Autism Spectrum Disorders. Method: a qualitative study, based on the Family-Centered Care philosophical theoretical framework and developed with 22 professionals from three multidisciplinary teams from the Health Care Network of a municipality in the state of Mato Grosso do Sul, Brazil. The data were collected through two focus groups with each team, organized with the support of the Atlas.ti 8 Qualitative Data Analysis® software and submitted to Thematic Content Analysis. Results: the findings show actions centered on specific situations, especially on the demands and needs arising from the child's care and atypical behavior. Influencing factors for family care, such as work overload and little professional experience, show the weakness of multiprofessional care and the invisibility of the family as a care unit. Conclusion: the need is highlighted to review functioning of the network for the multiprofessional care of children and their families and how such network is organized. It is recommended to offer permanent education actions that contribute to the qualification of multiprofessional teams in the care of families of children in the autism spectrum.